2009
DOI: 10.1002/bmc.1184
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance liquid chromatography method for determination of carnosic acid in rat plasma and its application to pharmacokinetic study

Abstract: A sensitive and reproducible high-performance liquid chromatography method with ultraviolet detection (UV) was developed for the determination of carnosic acid (CA) in rat plasma. After simple acidification and liquid-liquid extraction of plasma samples using gemfibrozil as an internal standard, the supernatant was evaporated to dryness under a gentle stream of nitrogen. The residue was reconstituted in 200 microL before being injected into the chromatographic system. The analysis was performed on a C(18) colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
(21 reference statements)
3
38
1
Order By: Relevance
“…The time-plasma concentration profiles of the present study are in agreement with the results found by Yan et al [15] where an IV and intra gastric administration was given of 10 and 90 mg CA/kg, to 5 and 8 rats, respectively. We fitted the time-concentration profile of the IV administrated rats to a two phase exponential decay curve instead of a single exponential model in the latter study.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The time-plasma concentration profiles of the present study are in agreement with the results found by Yan et al [15] where an IV and intra gastric administration was given of 10 and 90 mg CA/kg, to 5 and 8 rats, respectively. We fitted the time-concentration profile of the IV administrated rats to a two phase exponential decay curve instead of a single exponential model in the latter study.…”
Section: Discussionsupporting
confidence: 94%
“…However, a slow absorption of CA after PO administrations was found with a T max of 136.6 min, meaning that CA retained in the blood for a long time. In agreement, Yan et al [15] described that the absorption of CA after intragastric administration was slow (T max of 125.6 min). Since the results from the IV experiment showed that CA is eliminated from the blood rapidly, desorption of CA is thought to be rather slow.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, at concentrations used as a food additive, it is assumed that carnosic acid levels would not cause significant hepatotoxicity or DDI. However, at doses needed to elicit statistically significant weight loss and antiadipogenic effects in ob/ob mice (Wang et al, 2011), it is calculated that plasma concentrations in these animals would exceed 100 M based on the published pharmacokinetic parameters of carnosic acid in the rat (Yan et al, 2009;Doolaege et al, 2011). This concentration is equal to or greater than the carnosic acid concentrations used in the current human hepatocyte studies.…”
Section: Discussionmentioning
confidence: 98%
“…Carnosic acid concentration in rosemary ethanolic extract has been reported to be approximately 30 mg/gm fresh weight [40]. A pharmacokinetic study in SD rats revealed that CA is absorbed into the bloodstream after oral administration (90 mg/kg) with a high peak plasma concentration (*100 lM), which slowly declined with time remaining at the level of * 30 lM for at least 24 h [41]. Human clinical studies are yet to be carried out and therefore the bioavailability of CA in humans has not yet been established.…”
Section: Discussionmentioning
confidence: 98%